Geographic information system in assessing bruxism among school children (Research, Society and Development, 2022)
The aim of this study was to evaluate the distribution profile of childhood bruxism using Geographic Information System in the city of Alfenas, in southwest Brazil. The study included schoolchildren of both sex attending public schools in the city of Alfenas - Minas Gerais, Brazil. During clinical examination, the presence or absence of bruxism for each child was recorded. For statistical analysis, Chi-square test and t test was used to compare sex and age distribution according to the groups, with an established alpha of 5%. A Geographic Information System was used to perform the geoprocessing procedures. The home addresses were geocoded on a map to apply the kernel density estimator. The final sample includes 353 children, in which 44 presented signs of bruxism. Age and gender were not associated with bruxism (p>0.05). The spatial analysis of the distribution of childhood bruxism in the city of Alfenas indicated an occurrence of a hotspot. In conclusion, there is an intraurban differentials in childhood bruxism in the city.